Majority of Fortune 500 Companies in 2018 Did Not Recognize Risk of Epidemics Such as COVID-19 - MacDonald, Pia D. M.; Endres-Dighe, Stacy M.; Macoubray, Aaron J.; Shorey, Jamie M. (Frontiers in Public Health, 2021)
Infectious disease threats, like the 2002 severe acute respiratory syndrome coronavirus (SARS-CoV) disease, 2009 pandemic influenza A (H1N1), and the current coronavirus disease 2019 (COVID-19), pose multisectoral risk with the potential for wide-ranging socioeconomic disruption. In our globally intertwined economy, the impact of such events can elicit economic shock waves that reach far beyond the country of origin. Review of the 2018 Fortune 500 company 10-K filings shows the majority did not document perceived risks associated with epidemics, outbreaks, or pandemics. Enhanced engagement and investment of the public and private sectors in advancing global health security is needed to effectively prevent, detect, and respond to infectious disease events and ensure U.S. economic security.